Reviewing the Integration of RFID and IoT in Supply Chain Management: Enhancing Efficiency and Visibility - Al Mahmud, Md Abdullah; Hossan, Md Zikar; Tiwari, Anamika; Khatoon, Rabeya; Sharmin, Sadia; Hosain, Md Saddam; Ferdousmou, Jannatul (Journal of Posthumanism, 2025)
Supply Chain Management (SCM) increasingly relies on advanced technologies like Internet of Things (IoT) and Radio Frequency Identification (RFID) to enhance operational efficiency and decision-making processes. These technologies enable the integration of data, information, products, and physical objects throughout the supply chain, automating and optimizing business processes. IoT applications have revolutionized SCM by enabling smart objects that enhance intelligence and automation capabilities. The convergence of RFID with IoT, termed RFID-IoT, aims to develop automated sensing systems that are seamless, interoperable, and highly secure. This integration facilitates real-time tracking and monitoring of goods, improving supply chain visibility and responsiveness. The systematic review of current literature underscores RFID-IoT's potential to significantly enhance SCM by maximizing productivity, minimizing costs, and meeting customer requirements more effectively. However, challenges such as integration complexities and security issues remain critical areas for further research and development. Future advancements in RFID-IoT technologies promise to further streamline SCM processes across product manufacturing, shipping, distribution, inventory management, and retail, fostering a more efficient and resilient supply chain ecosystem.